Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska
Wydawnictwo:WSiP
Rok wydania:2016
Zapisz w postaci jednej potęgi o podstawie 4.58 gwiazdek na podstawie 12 opinii

`a) \ \ 2^3*4^2*8=2^3*(2^2)^2*2^3=2^3*2^4*2^3=2^(3+4+3)=2^10` 

`b) \ \ 27*9^3*3=3^3*(3^2)^3*3=3^3*3^6*3=3^(3+6+1)=3^10` 

`c) \ \ (1/5)^(-3)*25^2*5^4=5^3*(5^2)^2*5^4=5^3*5^4*5^4=5^(3+4+4)=5^11` 

`d) \ \ 7^(-3)*49^2*(1/7)^4=7^(-3)*(7^2)^2*7^(-4)=7^(-3)*7^4*7^(-4)=7^(-3+4+(-4))=7^(-3)` 

`e) \ \ ((2^3)^2*4^3)/8^3=(2^6*(2^2)^3)/((2^3)^3)=(2^6*2^6)/2^9=2^(6+6)/2^9=2^12/2^9=2^(12-9)=2^3` 

`f) \ \ ((9^2)^2*27)/3^5=(9^4*3^3)/(3^5)=((3^2)^4*3^3)/(3^5)=(3^8*3^3)/3^5=3^(8+3)/3^5=3^11/3^5=3^(11-5)=3^6` 

`g) \ \ (1/3)^(-2):3^2*9=3^2:3^2*3^2=3^(2-2+2)=3^2` 

`h) \ \ (2/3)^(-4):6^4/2^3=(3/2)^4:(2*3)^4/2^3=3^4/2^4*2^3/(2*3)^4=strike(3^4)^1/2^4*2^3/(2^4*strike(3^4)^1)=1/2^4*2^3/2^4=2^3/2^8-2^(3-8)=2^(-5)`